Factors that Influence Medication Compliance in Pulmonary Tuberculosis Patients - Bayu M.A Nugroho; Conita Yuniarifa; Kamilia Dwi Utami (Indonesian Journal of Global Health Research, 2025)
Pulmonary tuberculosis is a chronic infectious disease that has a significant impact on global health, including Indonesia. Bandar I Health Center, Batang Regency was chosen as the research location because it has a low complete rate of taking medication (29.09%). Objective to analyze factors that influence medication compliance in pulmonary tuberculosis patients, including knowledge, attitudes, access to health services, drug side effects, family support, and support from health workers. An analytical observational design with a cross-sectional method. Data were collected through questionnaires from 68 pulmonary tuberculosis patients who met the inclusion criteria. Bivariate analysis used the Chi-Square test to determine the relationship between each independent variable and compliance, while multivariate analysis was performed to determine the dominant influencing factors. The knowledge, attitude, family support, and health worker support had a significant relationship with patient compliance (p < 0.05). Health worker support was a dominant factor with an Exp(B) value of 28.7, which means that patients with good health worker support have a 28.7 times greater chance of compliance. In contrast, access to health services did not show a significant relationship (p > 0.05). The compliance of tuberculosis patient’s is influenced by education, positive attitude, family support, and attention from health workers. Interventions focused on strengthening patient education and increasing support from health workers are recommended to improve the success of tuberculosis treatment.